The Effect of Behavioral Interventions on Auditors' Knowledge-Sharing Behavior: Examining the Mediating Role of Attitudes and Normative Beliefs - Mahdis Nikzad Ghadikolaee (بررسی‌های حسابداری و حسابرسی, 2020)
Objective: The aim of this study was to investigate the effect of behavioral interventions on knowledge sharing behavior using the theory of planned behavior among independent auditors. Attitudes, abstract norms and inclinations are important aspects of this theory and their mediating role in the relationship between behavioral interventions and knowledge sharing behavior has also been investigated. Methods: The present study is applied and falls into the category of experimental research. The method of execution is multi-group post-test design. The statistical population of this study is the auditors working in the auditing organization and auditing institutes in Tehran. The sample is selected from the available sampling method and eliminated (screening). The of structural equations technique and non-parametric Kruskal-Wallis and Mann-Whitney tests have been used to test the research hypotheses. Results: The results show that behavioral interventions affect the knowledge-sharing behavior of independent auditors by influencing abstract attitudes and norms. In other words, abstract attitudes and norms play a mediating role in the relationship between behavioral interventions and knowledge sharing behavior. There is also a significant difference between the amounts of information shared by each group; Participants who received targeted messages about both behavioral and normative beliefs shared more information. Conclusion: Independent auditors have a positive attitude about knowledge sharing in their institutions and their mental norms are also influenced by a positive attitude towards knowledge sharing behavior. On the other hand, abstract attitudes and norms are reinforced by purposeful messages (behavioral interventions). These two factors have intensified their desire to share knowledge; But knowledge sharing behavior has not increased in line with this desire.